Ethno-Educational Governance Model: A Local Wisdom Approach To Strengthening Madrasah Quality - Ummi Royhana; Novi Darmayanti; Ah. Zakki Fuad (Universitas Pakuan, 2026)
This study aims to analyze and develop a Local Wisdom-Based Ethno-Educational Governance Model (EEGM) for strengthening madrasah quality at MA Irsyadun Nasyi'in Kasiyan Jember. The study was motivated by the need for an educational governance model that extends beyond administrative functions by integrating local cultural values, Islamic boarding school traditions, and Islamic educational management principles to enhance institutional quality. A qualitative approach was employed using a literature review combined with conceptual analysis of studies on Islamic educational management, organizational culture, local wisdom, and community-based educational governance. Data were collected from scientific journal articles, academic books, research reports, and other scholarly publications published between 2020 and 2025. Data analysis was conducted using descriptive-critical techniques, including data reduction, thematic categorization, conceptual interpretation, and theoretical synthesis. The findings indicate that the proposed EEGM consists of four key components: collective leadership based on shura (consultation), Islamic boarding school organizational culture, community participation grounded in social capital, and madrasah quality enhancement through local wisdom values. The integration of these components strengthens institutional identity, increases community participation, improves collaboration among stakeholders, and promotes a contextual, adaptive, and sustainable governance system. This study contributes to the development of culturally grounded Islamic educational management theory and provides practical recommendations for designing community-based policies to improve madrasah quality. Future studies should examine the implementation and effectiveness of EEGM in diverse madrasah settings and different local cultural contexts.